Electromagnetic interference shielding and electrical properties of nanocomposites based on poly (styrene-b-ethylene-ran-butylene-b-styrene) and carbon nanotubes. (April 2016) - Kuester, Scheyla; Barra, Guilherme M.O.; Ferreira, José Carlos; Soares, Bluma G.; Demarquette, Nicole R.
Graphical abstract: Highlights: Nanocomposites of SEBS/CNT were prepared by melt compounding. SEBS/CNT presented a low electrical percolation threshold of around 1 wt% of CNT. The electrical conductivity was enhanced by 17 orders of magnitude. EMI-SE of 30.07 dB (99.9% of incident radiation) was achieved with 15 wt% of CNT. Abstract: In this work, poly (styrene-b-ethylene-ran-butylene-b-styrene) and carbon nanotube (SEBS/CNT) nanocomposites were prepared by melt compounding for electromagnetic shielding applications. The structural characteristics and the morphology of carbon nanotubes (CNT) and nanocomposites were investigated using Raman spectroscopy and Field Emission Gun Scanning Electron Microscopy. The DC electrical conductivity of the nanocomposites was evaluated by two-probe and four-probe methods, and the electrical percolation threshold was calculated. Dielectrical properties, shielding mechanisms, and the electromagnetic interference shielding effectiveness (EMI-SE) of the nanocomposites were evaluated for the 8.2–12.4 GHz X-band microwave frequency range. A comparison between theoretical and experimental EMI-SE results was also reported. The nanocomposites studied exhibited a very sharp insulator-conductor transition at a CNT concentration of around 1 wt%, and the electrical conductivity increased by 17 orders of magnitude upon addition of more than 2 wt% CNT. Upon addition of 15 wt% of CNT, an EMI-SE of 30.07 dB, which corresponds to a reduction of 99.9% of the incident radiation, was obtained. The results indicate that the nanocomposites studied are promising candidates for electromagnetic shielding applications.